2018
DOI: 10.3988/jcn.2018.14.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Incidence, and Recurrence of Febrile Seizures in Korean Children Based on National Registry Data

Abstract: Background and PurposeFebrile seizures (FS) are the most common type of seizure during childhood, reportedly occurring in 2–5% of children aged 6 months to 5 years. However, there are no national data on the prevalence of FS in Korea. This study determined the prevalence, incidence, and recurrence rates of FS in Korean children using national registry data.MethodsThe data were collected from the Korea National Health Insurance Review and Assessment Service for 2009–2013. Patients with febrile convulsion as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 13 publications
3
31
1
4
Order By: Relevance
“…In this study, the overall prevalence of febrile seizure in the first five years of the observation period was 11.19%, which was higher than the worldwide incidence (2-5%) and that of Japan (9.3%), which is located geographically close to South Korea 1,2) . Byeon et al 8) reported that the prevalence of febrile seizure in Korean children younger than five years of age was 6.92% based on national cohort data, which was different from our result. We believe that this discrepancy is the result of the different inclusion criteria; we used R56.0x (febrile seizure) as an inclusion criterion, which has been used in many previous studies, whereas Byeon et al used R56.0x combined with G41.x (status epilepticus) or R56.8x (seizure) [7] [13].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, the overall prevalence of febrile seizure in the first five years of the observation period was 11.19%, which was higher than the worldwide incidence (2-5%) and that of Japan (9.3%), which is located geographically close to South Korea 1,2) . Byeon et al 8) reported that the prevalence of febrile seizure in Korean children younger than five years of age was 6.92% based on national cohort data, which was different from our result. We believe that this discrepancy is the result of the different inclusion criteria; we used R56.0x (febrile seizure) as an inclusion criterion, which has been used in many previous studies, whereas Byeon et al used R56.0x combined with G41.x (status epilepticus) or R56.8x (seizure) [7] [13].…”
Section: Discussioncontrasting
confidence: 99%
“…The incidence of febrile seizures varies geographically according to several studies, with incidence rates of 9.3% in Japan, 14% in Guam and 10% in India [2][3][4]. However, most previous studies were based on snapshot data from regional populations or hospital visits, and few population-based studies used longitudinal analysis from birth, especially in Korea [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…FS occurs in the absence of central nervous system (CNS) infection or acute imbalance of electrolytes without previous afebrile seizure in children aged more than 1 month 2 . According to documents, the prevalence of FS is almost 2%‐5% worldwide 3 …”
Section: Introductionmentioning
confidence: 99%
“…Febrile seizure (FS) is the most common type of seizure seen in children be tween 6 months to 5 years of age 1) . The average prevalence of FS in children younger than 5 years based on hospital visit rates in Korea was 6.92% between 2009 and 2013 2) . Although FS is benign and selflimited, it can frighten parents by the unusual appearance of their child.…”
Section: Introductionmentioning
confidence: 99%